Negative streamwise velocities and other rare events near the wall in turbulent flows - Lenaers, Peter; Li, Qiang; Brethouwer, Geert; Schlatter, Philipp; Orlu, Ramis (Journal of Physics: Conference Series, 2011)
Negative streamwise velocities, extreme wall-normal velocites and high flatness values for the wall-normal fluctuations near the wall are investigated for turbulent channel flow simulations at a series of Reynolds numbers up to Reτ = 1000 in this paper. Probability density functions of the wall-shear stress and velocity components are presented, as well as joint probability density functions of the velocity components and the pressure. Backflow occurs more often (0.06% at Reτ = 1000) and further away from the wall into the buffer layer for rising Reynolds number. An oblique vortex outside the viscous sublayer is found to cause this backflow. Extreme v events occur also more often for rising Reynolds number. Positive and negative velocity spikes appear in pairs, located on the two edges of a strong streamwise vortex: the negative spike occurring in a high speed streak indicating a sweeping motion, while the positive spike is located between a high and low speed streak. These extreme v events cause high flatness values near the wall (F(v) = 43 at Reτ = 1000).
CRIS-Team Scopus Importer:2023-03-21